Analisis Kelayakan Usaha Penggilingan Padi di Desa Wulanga Jaya Kecamatan Tikep Kabupaten Muna Barat - Yuliantari, Putu Mega; Gafaruddin, Abdul; Sadimantara, Fahria Nadiryati (Department of Agribusiness, Halu Oleo University, 2021)
This research aims to determine the feasibility of the rice milling business in Wulanga Jaya Village, Tikep District, West Muna Regency. The research location was determined purposively. The sampling technique in this research used saturated sampling, where all population members were sampled. The sample in this research was the owner of a rice mill business in Wulanga Jaya Village, Tikep District, West Muna Regency, and three businesses. The time of this research was carried out in May-October 2021. The variables in this research are, Respondent Identity which includes respondent's age, education level, length of business, number of family dependents, and Feasibility Analysis of Rice Milling Business which provides for total production costs, fixed costs, costs variables, revenue, income, NPV, IRR, Net B/C Ratio and Payback Period. Data analysis in this study uses the formula for income, revenue, and total production costs. The feasibility analysis used the calculation of NPV, IRR, Net B/C Ratio, and payback period. From the results of research using the feasibility analysis of the rice milling in Wulanga Jaya Village, Tikep District, West Muna Regency, it is feasible to run, and this can be seen from the total NPV calculation of IDR.26,702,563, IRR calculation of 17%> 12%, calculation of Net B/C Ratio 4.79 > one and analysis of Payback Period 4.6 years.